Comparing a Potential External Immune Defense Trait to Internal Immunity in Females of Wild Bumblebees - Baeuerle, Gitta; Feldhaar, Heike; Otti, Oliver (Frontiers in Ecology and Evolution, 2020)
External immune defense, such as antimicrobial secretions, is not generally viewed as part of the immune system. Nevertheless, it constitutes a first barrier to pathogens and manipulates microbial environments. Hygienic measures ranging from the protection of oneself or conspecifics, the nesting site, to stored food may be more efficient with secreted antimicrobials. However, the relationship between external immune defense and internal immunity, including potential life-history trade-offs, is not well understood. As hymenopteran venom often contains antimicrobial peptides it could serve as an external immune defense. Assuming that antimicrobial venom is costly its production might be traded-off against the internal immune defense. Here we compared the antimicrobial activity of venom and hemolymph in fourteen different bumblebee species according to their life-history strategies and characteristics, i.e. overwintered queens, workers and young queens and cuckoo queens. We found no direct relation between antimicrobial activity of hemolymph and venom. Across all species, hemolymph mainly showed lysozyme-like activity (LLA) whereas venom mainly showed antimicrobial peptide (AMP) activity. While LLA activity in the hemolymph was similar among species and life-history strategies and characteristics, both factors significantly differed in venom AMP activity. Independent of body size or fat body content, young queens showed the highest venom AMP activity, followed by workers, overwintered queens and cuckoo queens. Venom as a potential external immune trait seems not directly linked to internal immunity in bumblebees. However, the investment in external defense depends on the species and the life-history strategies and characteristics of an individual, such as social status or condition.